6. Strategies for Modelling the Educational Process from the Perspective of Internal Resources Stimulation of the Child - Zolotariov Elena; Foca Eugenia (Sciendo, 2017)
The article reflects an attempt to rethink the methodology of organizing the pedagogical process, oriented towards the development of "the humane in the person", shifting its focus onto stimulating children's inner resources. The emphasis is shifted from the teaching, learning and assessment processes, focused on research of the surrounding reality towards the exploitation of the child's innate potentials, the ability to know his inner world.